Stimulation of Eukaryotic DNA-Dependent RNA Polymerase by Protein Factors - Lee, Sheng-Chung (1973)
Protein factors that stimulate DNA-dependent RNA polymerase activity in vitro have been purified from Novikoff ascites cells. These factors are not adsorbed by the diethylaminoethylcellulose column used for RNA polymerase purification and appear in the flow-through fraction. They can be fractionated into two classes by chromatography on carboxymethylcellulose. The first peak of activity elutes at 0.1 M NH(4)Cl, is stable to heat treatment of 100° for 5 min, and is designated heat-stable factor; the second peak of activity elutes at 0.3 M NH(4)Cl, is heat labile, and is designated heat-labile factor. Heat-labile factor can be further resolved into two components by chromatography on phosphocellulose. The heat-stable factor and second heat-labile factor stimulate the activity of (Novikoff ascites) RNA polymerase B by several-fold, and appear to function independently. RNA synthesis is stimulated only with native DNA as a template. No stimulation of Escherichia coli RNA polymerase is observed with any of the factors.